Deriving Barbed Bisimulations for Bigraphical Reactive Systems - Grohmann, Davide; Miculan, Marino (Electronic Communications of the EASST, 2009)
We study the definition of a general abstract notion of barbed bisimilarity for reactive systems on bigraphs. More precisely, given a bigraphical reactive system, we define the corresponding barbs from the contextual labels given by the IPO construction, in a general and systematic way. These barbs correspond to observe which names on the interface are actually involved in reactions (and how).As examples, we apply this construction to the (bigraphical representation of the) pi-calculus and of Mobile Ambients, and compare the resulting barbed equivalences with those previously known for these calculi.